In vitro activity of nitroxoline against carbapenem-resistant Acinetobacter baumannii isolated from the urinary tract. (13th April 2022) - Fuchs, Frieder; Becerra-Aparicio, Federico; Xanthopoulou, Kyriaki; Seifert, Harald; Higgins, Paul G
Abstract: Background: The old antimicrobial nitroxoline is currently repurposed for oral treatment of uncomplicated urinary tract infections (UTIs). Objectives: To investigate the in vitro activity of nitroxoline against carbapenem-resistant Acinetobacter baumannii (CRAb). Methods: From an international collection of previously well-characterized clinical A. baumannii isolates, 34 isolates from urinary tract sources with different carbapenem-resistance mechanisms were selected. Nitroxoline activity was analysed with broth microdilution (BMD), disc diffusion (DD) and within an in vitro biofilm model. MICs of meropenem and imipenem were assessed with BMD. Susceptibility to ciprofloxacin and trimethoprim/sulfamethoxazole was investigated using DD. Escherichia coli ATCC 25922 and A. baumannii NCTC 13304 were used for quality control. Results: All isolates were carbapenem resistant (MIC90 >32 mg/L for meropenem and imipenem) and most isolates were resistant to ciprofloxacin (33/34) and trimethoprim/sulfamethoxazole (31/34). Nitroxoline yielded MIC50/90 values of 2/2 mg/L (MIC range 1–2 mg/L) and inhibition zone diameters ranging from 20 to 26 mm. In contrast, for definite eradication of biofilm-associated CRAb in vitro, higher nitroxoline concentrations (≥16 to ≥128 mg/L) were necessary for all isolates. Conclusions: Nitroxoline showed excellent in vitro activity against a collection of CRAb despite high resistance rates to other antimicrobials for parental and oral therapy of A. baumannii UTI. Currently, nitroxoline is recommended for the treatment of uncomplicated UTI in Germany with a EUCAST breakpoint limited to uncomplicated UTI and E. coli (S ≤16 mg/L). Nitroxoline could be a promising drug for oral treatment of lower UTI caused by CRAb. More data are warranted to correlate these findings with in vivo success rates.